Specific and sensitive GC–MS analysis of hypusine, Nε-(4-amino-2-hydroxybutyl)lysine, a biomarker of hypusinated eukaryotic initiation factor eIF5A, and its application to the bi-ethnic ASOS study - Baskal, Svetlana; Kaiser, Annette; Mels, Catharina; Kruger, Ruan; Tsikas, Dimitrios (Amino acids, 2022)
Hypusination is a unique two-step enzymatic post-translational modification of the N ε -amino group of lysine-50 of the eukaryotic initiation factor 5A (eIF5A). We developed a specific and sensitive gas chromatography–mass spectrometry (GC–MS) method for the measurement of biological hypusine (Hyp), i.e., N ε -(4-amino-2-hydroxybutyl)lysine. The method includes a two-step derivatization of Hyp: first esterification with 2 M HCl in CH 3 OH (60 min, 80 °C) to the methyl ester (Me) and then acylation with penta-fluoro-propionic (PFP) anhydride in ethyl acetate (30 min, 65 °C). Esterification with 2 M HCl in CD 3 OD was used to prepare the internal standard. The major derivatization product was identified as the un-labelled (d 0 Me) and the deuterium-labelled methyl esters (d 3 Me) derivatives: d 0 Me-Hyp-(PFP) 5 and d 3 Me-Hyp-(PFP) 5 , respectively. Negative-ion chemical ionization generated the most intense ions with m / z 811 for d 0 Me-Hyp-(PFP) 5 and m / z 814 for the internal standard d 3 Me-Hyp-(PFP) 5 . Selected-ion monitoring of m / z 811 and m / z 814 was used in quantitative analyses. Free Hyp was found in spot urine samples (10 µL) of two healthy subjects at 0.60 µM (0.29 µmol Hyp/mmol creatinine) in the female and 1.80 µM (0.19 µmol Hyp/mmol creatinine) in the male subject. The mean accuracy of the method in these urine samples spiked with 1–5 µM Hyp was 91–94%. The limit of detection (LOD) of the method is 1.4 fmol Hyp. The method was applied to measure the urinary excretion rates of Hyp in healthy black ( n = 38, age 7.8 ± 0.7 years) and white ( n = 41, age 7.7 ± 1.0 years) boys of the Arterial Stiffness in Offspring Study (ASOS). The Hyp concentrations were 3.55 [2.68–5.31] µM (range 0.54–9.84 µM) in the black boys and 3.87 [2.95–5.06] µM (range 1.0–11.7 µM) in the white boys ( P = 0.64). The creatinine-corrected excretion rates were 0.25 [0.20–0.29] µmol/mmol (range 0.11–0.36 µmol/mmol) in the black boys and 0.26 [0.21–0.30] µmol/mmol (range 0.10–0.45 µmol/mmol) in the white boys ( P = 0.82). These results suggest that there is no ethnic-related difference in the ASOS population in the eIF5A modification. Remarkable differences were found between black and white boys with respect to correlations of urinary Hyp with amino acids and advanced glycation end-products of Lys, Arg and Cys. Deoxyhypusine, formally the direct precursor of Hyp, seems not to be excreted in the urine by healthy subjects.